Analysis of the Generation of Harmful Aldehydes in Edible Oils During Sunlight Exposure and Deep-Frying Using High-Field Proton Nuclear Magnetic Resonance Spectroscopy - Anna Meike Freis; Sahithya Phani Babu Vemulapalli (Foods)
Edible oils are essential dietary components that provide crucial micronutrients. However, their quality can deteriorate during frying—a common cooking method—and with prolonged light exposure due to chemical reactions such as hydrolysis, oxidation, and polymerization. These processes lead to the formation of harmful compounds, particularly aldehydes. This study investigates how thermal and light exposure impact the chemical composition of five widely used edible oils: olive, rapeseed, sunflower, sesame, and peanut oils. For the thermal treatment, the oils were heated to 190 ± 5 °C in a commercial fryer, with samples taken at the start and after 10 min and 60 min of heating, while intermittently frying chicken nuggets to simulate typical frying conditions. For the light exposure treatment, the oil samples were exposed to direct sunlight for 3 and 8 h, with control samples being collected beforehand. The oil composition was analyzed using an advanced 800 MHz nuclear magnetic resonance (NMR) instrument with a triple-resonance inverse cryoprobe, providing high sensitivity and resolution. The results revealed a significant increase in various aldehyde compounds in all oils under both thermal and light exposure conditions. Notably, this study identified the generation of genotoxic and cytotoxic α,β-unsaturated aldehydes, including 4-hydroperoxy-(E)-2-alkenals, 4-hydroxy-(E)-2-alkenals, and 4,5-epoxy-(E)-2-alkenals. Given the established association of aldehydes with health risks, including cancer, Alzheimer’s, and Parkinson’s diseases, these findings highlight the importance of monitoring oil degradation during cooking and the appropriate storage of oils to minimize light exposure to reduce potential health risks.